2021
DOI: 10.1016/j.csbj.2021.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the immune landscape in virus-induced cancers using a novel integrative mechanism discovery approach

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Despite the well understood differences in the pathological [ 41 , 42 ] and clinical outcomes [ 43 , 44 , 45 ] between EBVaGCs and EBVnGCs, comparisons of their respective tumor immune microenvironments are generally restricted to a subset of markers in a subset of subtypes [ 46 , 47 , 48 , 49 , 50 ]. There is ever increasing evidence that patient outcomes are greatly impacted by the interactions of tumors with their local immune microenvironments [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well understood differences in the pathological [ 41 , 42 ] and clinical outcomes [ 43 , 44 , 45 ] between EBVaGCs and EBVnGCs, comparisons of their respective tumor immune microenvironments are generally restricted to a subset of markers in a subset of subtypes [ 46 , 47 , 48 , 49 , 50 ]. There is ever increasing evidence that patient outcomes are greatly impacted by the interactions of tumors with their local immune microenvironments [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…From pathway enrichment analysis, we found that early stages of invasive CeCa differed from their non-invasive precursor lesions in marked up-regulation of innate immunity pathways, particularly antiviral mechanisms mediated by DNA-sensors, and involvement of IFN-stimulated, pro-inflammatory, as well as DDR-related genes. This probably implies that overstimulation of protective mechanisms in early periods may be one of the triggers and contributors of invasion; at subsequent stages this could become manifest in the form of an immune-active but chronically inflamed and exhausted molecular subtype (43)(44)(45). Relatedness of the DDR-associated processes and "heating-up" the immune TME has also been underscored by some researchers (42,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…CC ranks in the top ten female cancers in incidence and mortality in California and Texas [ 1 ]. Various studies have shown that the alteration in gene expression is an important event in CC [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%